Joint routing, band, and spectrum assignment in C+L band elastic optical networks towards ultra-broadband era - Zheng, Weichang; Yang, Mingcong; Zheng, Yu; Zhang, Yongbing; Yang, Kun (Computer networks (Amsterdam, Netherlands : 1999), 2025)
The rapid growth in Internet traffic is pushing single-fiber capacity closer to its Shannon limit, highlighting the need for advancements in optical communication technologies. Elastic Optical Networks (EONs) have emerged as a promising solution to improve spectral efficiency. Another method to expand capacity is by using both C and L bands, instead of relying solely on the C band, thereby expanding the available spectrum. However, the introduction of new transmission technologies and the expansion of spectrum resources necessitate operators to re-plan networks in a cost-effective manner. In this paper, we propose a two-layer network architecture that separates the C-band and L-band. Given that the optical parameters of these bands differ, it becomes essential to allocate routing and resources dynamically based on varying traffic demands. We define this problem as the Routing, Band, and Spectrum Assignment (RBSA) problem and prove its NP-hardness. To address it, we introduce an Integer Linear Programming (ILP) model aimed at minimizing capital expenditure (CAPEX), along with a heuristic algorithm for large-scale instances. Simulation experiments using different sizes of service request matrices on two network topologies demonstrate the effectiveness of both the ILP model and the heuristic algorithm. To the best of our knowledge, this is the first work that addresses the RBSA problem in C+L band EONs.